Financial Distress Using the Zmijewski, Grover, and Springate Models at Retail Business in Indonesia - Fitriyah, Erni Muti’atul; Prasasti, Karari Budi (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: This study aims to analyze PT Matahari Putra Prima's financial health during 2018-2022 using the Zmijewski, Grover, and Springate models to predict potential financial distress. Background Problems: When a company experiences bankruptcy, its financial statements must be evaluated and measured through in-depth research. PT Matahari Putra Prima Tbk, a major player in Indonesia's retail industry, has faced significant challenges over the past few years due to shifts in consumer behavior towards online shopping and the economic impacts of COVID-19. Novelty: This research fills the gap in financial distress in retail businesses in Indonesia. Research Methods: This study uses a descriptive quantitative approach. The financial data of PT Matahari Putra Prima Tbk from 2018 to 2022, obtained through documentation and literature review, were analyzed using three financial distress models: Zmijewski, Grover, and Springate. The sampling technique is a sampling technique to be used in research. The sampling design of this study uses nonprobability sampling. Nonprobability sampling can provide very useful information for a population. Following this study, the author will use the purposive sampling technique. Finding/Results: PT Matahari Putra Prima Tbk for five years for 2018 – 2022 using Zmijewski, Grover, and Springate indicated that the company was experiencing Financial Distress. Research limitation/implications: It is better for PT. Matahari Putra Prima Tbk evaluates financial performance to bring the company to a better state. The company's value that shows the risk of financial distress, PT Matahari Putra Prima Tbk, focuses more on improving operational efficiency and reducing costs in improving cash management and reducing short-term debt to reduce the risk of financial distress. Furthermore, maintain good communication with investors and stakeholders to build trust and support.